An Introduction to Child Development (Sage Publications, 2006)
This textbook offers an engaging and comprehensive introduction to the study of child development.Foreword, The Principles of Developmental Psychology, Theories of Development, Research Methodology in Developmental Psychology, The Biological Foundations of Development, Perceptual Development, Cognitive Development, The Development of Language and Communication, Emotional Development, Social Development, Developmental Psychopathology, Afterward, References, Index.